Persepsi Strategi Produk, Penetapan Harga, Dan Komunikasi Pemasaran Terhadap Pemasaran Dalam Posisi Kompetitif Café Peraduan - Sari Wiyanti; Mas Yusuf Sugiarto; Muhammad Faada Insani (Indo Publishing, 2025)
The cafe industry is experiencing rapid growth as a gathering place for the younger generation, which requires the implementation of efficient marketing strategies to achieve competitiveness. Therefore, Café Peraduan needs to identify how consumers view product strategy, pricing, and marketing communications to strengthen its position in the market. This study adopted a quantitative approach using a questionnaire survey method involving 102 Café Peraduan consumers who had made at least three purchases (purposive sampling method), which were then analyzed using multiple linear regression through SPSS version 25. This analysis includes normality tests, heteroscedasticity, multicollinearity, t-test, F-test, and calculating the coefficient of determination. The results of the analysis show that product strategy (sig. 0.002), pricing (sig. 0.000), and marketing communications (sig. 0.020) have a partial significant influence on competitive position. In addition, simultaneously also shows significant results (F sig. 0.000) with an adjusted R square of 29.4% and a regression model of (β = 0,229; Sig = 0,002), (β = 0,338; Sig = 0,000), dan (β = 0,205; Sig = 0,020). From these findings, it can be concluded that the three strategies significantly contribute to improving the competitive position of Café Peraduan, with future suggestions to explore additional variables to understand the remaining 70.6% of variation.